2007
DOI: 10.1111/j.1468-1293.2007.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of M184I/V in minor HIV‐1 populations of patients with lamivudine and/or didanosine treatment failure

Abstract: ObjectivesThe aim of the study was to investigate the presence of M184I/V in minor HIV-1 populations of patients who failed lamivudine (3TC) and/or didanosine (ddI) treatment. Materials and methodsFourteen 3TC-experienced patients who, after switching therapy to a ddI regimen, had a new failure without M184I/V in the major viral population were included in the study. Ninety plasma samples were analysed by direct sequencing and selective real-time polymerase chain reaction (SPCR), which detects GTG/GTA and ATA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…As expected [13,15], SPCR detected the M184V mutants in all samples that were positive by direct sequencing. In samples lacking M184I/V or with different proportions of the mutants in the plasma and CSF viruses, it must be emphasized that these results could have been influenced by the relatively low HIV‐1 RNA load found in some samples.…”
Section: Discussionsupporting
confidence: 86%
“…As expected [13,15], SPCR detected the M184V mutants in all samples that were positive by direct sequencing. In samples lacking M184I/V or with different proportions of the mutants in the plasma and CSF viruses, it must be emphasized that these results could have been influenced by the relatively low HIV‐1 RNA load found in some samples.…”
Section: Discussionsupporting
confidence: 86%
“…Y115 (green) appears to play a key role as a gate, discriminating dNTPs from rNTPs (Boyer et al, 2000; Gao et al, 1997; Joyce, 1997; Martín-Hernández, Domingo, and Menéndez-Arias, 1996). Mutations at residue M184 (purple), which naturally contributes to mismatch selectivity, are frequently found in HIV-1 drug resistant patients (Menéndez-Arias, 2008; Pandey et al, 1996; Ray, Basavapathruni, and Anderson, 2002; Svedhem et al, 2007; Yang et al, 2008; Yoshimura et al, 1999). M184I, for example, is a transient 3TC resistant mutation, ultimately resulting in M184V (Frost et al, 2000; Mulder, Harari, and Simon, 2008; Svedhem et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations at residue M184 (purple), which naturally contributes to mismatch selectivity, are frequently found in HIV-1 drug resistant patients (Menéndez-Arias, 2008; Pandey et al, 1996; Ray, Basavapathruni, and Anderson, 2002; Svedhem et al, 2007; Yang et al, 2008; Yoshimura et al, 1999). M184I, for example, is a transient 3TC resistant mutation, ultimately resulting in M184V (Frost et al, 2000; Mulder, Harari, and Simon, 2008; Svedhem et al, 2007). It was found that the beta branched side chain of isoleucine sterically blocks the entry of 3TC into the active site of RT (Sarafianos et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still not clear to which extent infection of new cells occurs during the phase of viral decay after initiation of suppressive ART, and whether viral replication can lead to the early selection of drugresistant viruses. When treatment failure occurs after a period of undetectable viremia, minority drug-resistant quasispecies can emerge as the major viral population [Metzner et al, 2003;Charpentier et al, 2004;Roquebert et al, 2006;Svedhem et al, 2007]. These variants can either be pre-existing or evolve in the setting of incomplete viral suppression.…”
Section: Introductionmentioning
confidence: 99%